The Development of the Soul in Early Childhood: A Model Based on Ibn Sina's Theory of the Soul in Islamic Philosophy - Nurul Ain binti Norman; Ahmad Zuhdi Bin Ismail; Zaharah Binti Hussin; Mohammad Eisa Ruhullah (al-Afkar, Journal For Islamic Studies, 2024)
Discover the profound impact of Islamic philosophy on soul development during early childhood with a model based on the renowned Ibn Sina's theory of the soul. Explore the thought-provoking insights and practical applications of this model that can help shape the minds and lives of young ones. Trust in the wisdom of the ancient Islamic philosophers and their groundbreaking theories that have stood the test of time. Gain a deeper understanding of the importance of nurturing the soul in the formative years and start a journey towards a more enlightened approach to child-rearing. This article uses a qualitative-descriptive approach involving a literature review and comparative analysis based on Ibn Sinā's works. The primary research method employed in this study is the Design and Development Research (DDR) method. This method involves a systematic investigation of the design and principles of the CSD Model. The research activities include developmental research stages using the Fuzzy Delphi Method. The study found that the text explores the concepts of religious education, emotional intelligence, and spiritual intelligence, highlighting the significance of emotional and spiritual literacy in children's education. It also discusses the CSD model proposed by Ibn Sina, which provides a hierarchical structure of the soul's different functions and levels, emphasizing physical, emotional, and intellectual integration within human beings. Furthermore, it discusses the crucial elements that parents believe are necessary for their children's spiritual development, including love and nurturing, values and morals, spirituality and faith, sense of identity, resilience and emotional intelligence, education and intellectual growth, compassion and empathy, freedom and independence, nature, and connection to the world, and relationships and social skills.